Alternating copolymerization of epoxides with carbon dioxide or cyclic anhydrides using bimetallic nickel and cobalt catalysts: Preparation of hydrophilic nanofibers from functionalized polyesters. (11th April 2018) - Chang, Chi-Hang; Tsai, Chen-Yen; Lin, Wei-Jen; Su, Yu-Chia; Chuang, Hui-Ju; Liu, Wan-Ling; Chen, Chi-Tien; Chen, Chih-Kuang; Ko, Bao-Tsan
Abstract: A series of di-nuclear metal acetate complexes1 –6 incorporated by nitrogen heterocycle-containing salen-type ligands have been synthesized, structurally characterized and performed as catalysts to prepare biodegradable polycarbonates and polyesters. Their catalytic performances for copolymerization of carbon dioxide-epoxides or cyclic anhydride-epoxides were systematically examined. Bimetallic nickel(II) complexes1, 2 and5 were active catalysts for the alternating copolymerization of cyclohexene oxide (CHO) with CO2 ; di-nickel complex1 was shown to be the most effective and selective, leading to obtaining poly(cyclohexene carbonate)s with the best efficiency among them. Moreover, complex1 was also found to be versatile for the ring-opening copolymerization of CO2 with different cyclic epoxides to give the corresponding polycarbonates. Additionally, di-cobalt(II) analogs3, 4 and6 were efficient catalysts for the alternating copolymerization of CHO and phthalic anhydride (PA) under mild conditions. Based on the results of catalytic studies, complex3 was demonstrated to be the most active one CHO-PA copolymerization, producing the polymeric products with a "controlled" manner involving controllable molecular weights and narrow polydispersity. Interestingly, Co complex3 was also able to catalyze the copolymerization of PA with 4-vinyl-1, 2-cyclohexene oxide to obtain the associated polyester with the vinyl functionality on the side chains, which was further functionalized with tertiary amine moieties via thiol-ene click functionalization and converted to nanofibers through electrospinning. Due to the incorporation of polar groups, the resulting tertiary amine-modified polyester nanofibers that exhibit an improved hydrophilic property relative to their un-modified counterpart have been considered to have high potential to be utilized as a new functional fiber material. Graphical abstract: New bimetallic bis(benzotriazole iminophenolate) or bis(benzothiazole iminophenolate) nickel and cobalt complexes were developed for versatile ROCOP of internal epoxides with CO2 or phthalic anhydride (PA). Particularly, di-Co complex3 was able to copolymerize 4-vinyl-1, 2-cyclohexene oxide with PA to afford the vinyl-functionalized polyester, which could be further utilized for the preparation of hydrophilic nanofiber via functional modification and electrospinning. Highlights: Well-defined dinuclear Ni and Co catalysts bearing BiIBT(h)P ligands were developed. Versatile catalysis for ROCOP of cyclic epoxides with CO2 or PA was studied. Di-Ni1 could efficiently catalyze CO2 -copolymerization of CHO, VCHO or CPO. Alternating poly(PA- alt -VCHO)s were prepared on PA/VCHO copolymerization by di-Co3. The functionalized poly(PA- alt -VCHO) could be converted to NFMs via electrospinning.